An investigation of carbon dioxide capture by chitin acetate/DMSO binary system. (5th November 2016) - Eftaiha, Ala'a F.; Alsoubani, Fatima; Assaf, Khaleel I.; Troll, Carsten; Rieger, Bernhard; Khaled, Aseel H.; Qaroush, Abdussalam K.
Graphical abstract: Highlights: Carbon capture at ambient conditions using chitin acetate/DMSO binary system. CO2 capture using bio-renwables following "Supramolecular Chemistry". DFT calculations for the justification of structure activity relationships. Benign conditions for postcombustion process. Superior sorption capacity and low production cost compared to others. Abstract: Chitin is considered to be the second most abundant naturally-occurring polysaccharide. Also, dimethyl sulfoxide (DMSO) is the second highest dielectric constant polar solvent after water. Despite the low solubility of chitin in common organic solvents, and due to its high nitrogen content, it may serve as a potential scrubbing agent "wet scrubbing" for carbon dioxide (CO2 ) capturing as an alternative to monoethanolamine " renewables for renewables approach" . Briefly, a detailed investigation for the utilization of low molecular weight, chitin-acetate (CA) in DMSO for the capturing of CO2 is reported. As carbonation process takes place, the formation of ionic alkylcarbonate was confirmed throughout spectroscopic and computational studies. Supramolecular chemisorption was proven throughout 1 H Nuclear Magnetic Resonance ( 1 H NMR) together with the absence of sorption of CO2 by the monomeric repeating unit, glucosamine hydrochloride. Further, Density Functional Theory (DFT) calculations supported the formation of the CA/CO2 adduct through a newly formed supramolecular ionic interaction and hydrogen bonding along the oligosaccharide backbone between the neighboring ammonium ion and hydroxyl functional groups. The sorption capacity was measured volumetrically within an in situ Attenuated Total Reflectance-Fourier Transform Infrared coupled ( in situ ATR-FTIR) autoclave at 25.0 °C, and 4.0 bar CO2, with a maximum sorption capacity of 3.63 mmol CO 2 /gsorbent at 10.0% (w/v).